Disruption of PAMP-Induced MAP Kinase Cascade by a Pseudomonas syringae Effector Activates Plant Immunity Mediated by the NB-LRR Protein SUMM2 - Zhang, Zhibin; Wu, Yaling; Gao, Minghui; Zhang, Jie; Kong, Qing; Liu, Yanan; Ba, Hongping; Zhou, Jianmin; Zhang, Yuelin (Cell host & microbe, 2012)
Pathogen-associated molecular pattern (PAMP)-triggered immunity (PTI) serves as a primary plant defense response against microbial pathogens, with MEKK1, MKK1/MKK2, and MPK4 functioning as a MAP kinase cascade downstream of PAMP receptors. Plant Resistance (R) proteins sense specific pathogen effectors to initiate a second defense mechanism, termed effector-triggered immunity (ETI). In a screen for suppressors of the mkk1 mkk2 autoimmune phenotype, we identify the nucleotide-binding leucine-rich repeat (NB-LRR) protein SUMM2 and find that the MEKK1-MKK1/MKK2-MPK4 cascade negatively regulates SUMM2-mediated immunity. Further, the MEKK1-MKK1/MKK2-MPK4 cascade positively regulates basal defense targeted by the Pseudomonas syringae pathogenic effector HopAI1, which inhibits MPK4 kinase activity. Inactivation of MPK4 by HopAI1 results in activation of SUMM2-mediated defense responses. Our data suggest that SUMM2 is an R protein that becomes active when the MEKK1-MKK1/MKK2-MPK4 cascade is disrupted by pathogens, supporting the hypothesis that R proteins evolved to protect plants when microbial effectors suppress basal resistance. ► The MEKK1-MKK1/MKK2-MPK4 kinase cascade is required for basal defense ► MEKK1-MKK1/MKK2-MPK4 cascade negatively regulates NB-LRR protein SUMM2-mediated immunity ► The bacterial pathogenic effector HopAI1 targets MPK4 kinase activity ► Inactivation of MPK4 by HopAI1 activates SUMM2-mediated immune responses